Widely tunable multi-wavelength Brillouinerbium fiber laser utilizing low SBS threshold photonic crystal fiber - Nasir M.N.M.; Yusoff Z.; Al-Mansoori M.H.; Rashid H.A.A.; Choudhury P.K. (Optical Society of America (OSA), 2023)
A widely tunable low stimulated Brillouin scattering (SBS) photonic crystal fiber (PCF) based multi-wavelength Brillouin-erbium fiber laser is presented. The fiber laser structure utilizes a pre-amplified Brillouin pump (BP) technique with 100 m of PCF and a tunable band-pass filter within a Fabry-Perot cavity. A total of 14 Brillouin Stokes lines can be tuned over 29 nm from 1540 nm to 1569 nm. The wide tunability was only limited by the bandwidth of the tunable band-pass filter. A constant channel spacing of 0.079 nm and signal to noise ratio (SNR) of more than 20 dB for each Brillouin Stokes lines were also observed. 2009 Optical Society of America.